Dietary micronutrients and in vivo n-3 LC-PUFA biosynthesis in Atlantic salmon - SS Giri; J Graham; NKA Hamid; John Donald; GM Turchini (2016)
Aquaculture, and in particular Atlantic salmon culture, is expected to deliver n. -3 long-chain polyunsaturated fatty acid (n. -3 LC-PUFA) rich products. Nevertheless, the availability of n. -3 LC-PUFA rich raw materials for aquafeed is dwindling, and at an ever increasing market price. Thus, there is the need to better understand the in vivo n. -3 LC-PUFA biosynthetic capabilities of cultured fish to enable the possible maximization of dietary 18:3n. -3 (ALA) bioconversion to 20:5n. -3 (EPA) and 22:6n. -3 (DHA). The cofactors and coenzymes involved in this metabolic pathway have so far received limited research attention. In this study, juvenile Atlantic salmon were fed an ALA-rich diet with no, normal, or over-fortified inclusion of those micronutrients reported to be essential cofactors (iron; zinc; magnesium) and coenzymes (riboflavin; biotin; niacin) for the fatty acid elongase and desaturase enzymes. The results showed that reduced dietary inclusion of these micronutrients impaired the normal n. -3 LC-PUFA biosynthetic capabilities of fish, whereas the over fortification did not provide any additional benefit. This study provides new knowledge on micronutrients and lipid metabolism interactions in a commercially important cultured species, and is envisaged to be a useful contribution towards developing more sustainable and commercially viable aquafeed for the future.Statement of relevance. This work is the continuation and extension of a previous study (Lewis et al., 2013, Aquaculture 412/413, 215-222) in which we explored the physiological roles and potential effects of micronutrients on fatty acid metabolism in cultured fish. The present study differed from the previous in the blend of minerals and vitamins used, the species, the fatty acid composition of the test diet, and the inclusion also of a negative control. The results are most interesting, showing that riboflavin (B2), biotin (B7), and niacin (B3), Iron (Fe), Magnesium (Mg) and Zinc (Zn) are all required for proper fatty acid bioconversion, but ...